QUANTITATIVE COMPOSITION OF CHEMICAL ELEMENTS AND VITAMINES OF PHLOMOIDES SPECIOSA (Scientific journal of the Fergana State University, 2024)
The article presents the results of experimental determination of the quantitative composition of 44 elements in flowers, stems and leaves of the Phlomoides speciosa plant using the ICP-MS inductively coupled plasma mass spectrometry method. NEXION-2000 equipment was used. Main quantitative components in flowers: Potassium, K 5487,875; Phosphorus, P 3791,449; Magnesium, Mg 1849.238; Calcium, Ca 1325,689. These elements are also the main elements in leaves and stems, but potassium and calcium are 7-8 times more abundant in stems.   The amount of vitamins in plant raw materials was determined by the HPLC method. It was shown that the main quantitative component is ascorbic acid (2.0784 mg/g) and the largest amount of adermin (1.8146 mg/g) of substances belonging to the group of four B vitamins.